Etika dan sosial dalam manajemen keuangan syariah - Maulidiana, Ade Ega (Maliki Interdisciplinary Journal, 2024)
Sharia financial management is an approach to managing financial resources based on Islamic principles. Its main foundations are the prohibitions of riba (interest), gharar (excessive uncertainty), and maysir (gambling). Sharia financial management uses financial instruments such as mudharabah (profit-sharing), musyarakah (partnership), murabahah (sale with agreed profit), ijarah (leasing), and sukuk (Islamic bonds). Social and ethical aspects are also considered, such as zakat (obligatory alms), waqf (endowment for public interest), and corporate social responsibility. The Islamic finance industry has grown rapidly across the globe, but its main challenge is ensuring compliance with Sharia principles in every financial transaction. The aim of this article is to describe the ethical and social aspects of Sharia financial management. The method used is a literature review, collecting various relevant sources. The article concludes that ethical and social considerations significantly influence Sharia financial management.